Non-financial reporting: Standardization options for SME sector - Patrycja Krawczyk (Journal of Risk and Financial Management, 2021)
Non-financial reporting is the basic tool for presenting the implementation of sustainability goals (SDGs). This paper investigated the current status of non-financial reporting standardization in terms of small and medium-sized enterprises. The topic of non-financial reporting has been discussed in recent years from the perspective of large business entities. So far, it has only rarely been applied to SMEs. This will increase significantly in the coming years when such reports will also become obligatory for smaller entities. The first stage of the research, based on the method of analysis and criticism of the literature, will be prepared in the area of the subject taken, including relations between the main concepts: sustainability, non-financing reports, SMEs. The essential data source used for the article is reports published by the Global Reporting Initiative. Based on the research conducted, it can be concluded that it is necessary to develop non-financial reporting standards for SMEs. These results may become a valuable resource of knowledge and a set of samples that can be useful in developing this area. Especially since it can be expected that such reports will also be obligatory for SMEs.
Keywords: 330; sustainability; corporate social responsibility (CSR); non-financial report; small and medium-sized enterprises (SME); standardization; sustainability goals (SDGs)